2013
DOI: 10.1158/1055-9965.epi-12-1211
|View full text |Cite
|
Sign up to set email alerts
|

Family History of Colorectal Cancer in BRAF p.V600E-Mutated Colorectal Cancer Cases

Abstract: Background Previous reports suggest that relatives of CRC-affected probands carrying the BRAF p.V600E mutation are at an increased risk of colorectal (CRC) and extracolonic cancers (ECCs). In this study, we estimated the association between a family history (FH) of either CRC or ECC and risk of CRC with a BRAF p.V600E mutation. Methods Population-based CRC cases (probands; aged 18–59years at diagnosis), recruited irrespective of family cancer history, were characterised for BRAF p.V600E mutation and mismatch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…A subset of this data has been previously reported highlighting an inverse association between BRAF-mutated CRC and family history of CRC. 27 In contrast, three other studies support an association between a family history of CRC and an increased risk of the BRAF-mutated CRC. [55][56][57] One potential explanation for the discrepancy in findings between this study and the previous reports might be the difference in the mean age at diagnosis of the CRC cases.…”
Section: Discussionmentioning
confidence: 94%
“…A subset of this data has been previously reported highlighting an inverse association between BRAF-mutated CRC and family history of CRC. 27 In contrast, three other studies support an association between a family history of CRC and an increased risk of the BRAF-mutated CRC. [55][56][57] One potential explanation for the discrepancy in findings between this study and the previous reports might be the difference in the mean age at diagnosis of the CRC cases.…”
Section: Discussionmentioning
confidence: 94%
“…Our results are similar to those of Kwon et al [28] who found that the prevalence of BRAF mutations in 92 CRC patients was 3.3% using the PNA-mediated PCR clamping method. BRAF mutations have been associated with inferior survival for CRC [37,38,39] and a reduced likelihood of a family history of CRC in a young age group [40]. Zlobec et al [41] showed the coexistence of high-level CpG island methylator phenotype (CIMP) with BRAF mutation.…”
Section: Discussionmentioning
confidence: 99%
“…A fluorescent allele-specific PCR assay was used to detect the somatic T>A mutation at nucleotide 1799 in exon 15 of the BRAF gene ( BRAF V600E) as has been previously described [22, 23]. Methylation of the MLH1 gene promoter was measured in all MSI-high and MSI-low cases with sufficient tumor DNA and a random sample of microsatellite stable cases.…”
Section: Methodsmentioning
confidence: 99%